Transient flow in a compressor blade row for a periodic vibration motion - Idres, Moumen; Labanie, Mohamed; Okasha, Mohamed Elsayed Aly Abd Elaziz (IOP Publishing, 2018)
The goal of this work is to conduct a transient compressor blade row flow simulation as part of blade flutter modeling. An integral step of blade flutter modeling is the calculation of the aerodynamic damping factor as a function of the possible vibration mode shapes. Using Fourier method, the number of blade passages required for transient flow analysis is kept to a minimum of two for all vibration modes. In this work, a compressor rotor blade row is considered. The vibration modes are obtained using ANSYS mechanical, then, unsteady flow is obtained for vibrating blades with a harmonic motion. Work of the flow on the blade is calculated and hence the aerodynamic damping is obtained.